Primary T-cell lymphoblastic lymphoma of the ovary: A case report - Sweta Singh; Susama Patra; Narbadyswari Deep Bag; Monalisha Naik (Indian Journal of Medical and Paediatric Oncology)
Primary ovarian lymphoma is extremely rare. We report a case of primary T-cell lymphoblastic lymphoma of the ovary in a 31-year-old multiparous woman, who presented with abdominal pain. Her menstrual cycles were regular. There was no generalized lymphadenopathy or fever. On per abdominal examination, there was a firm, tender, solid, mobile mass with well-defined borders, corresponding to 20 weeks gestation, whose lower pole was easily reached. Per vaginum examination revealed a large adnexal mass in the right and anterior fornix. Transabdominal ultrasonography showed bilateral solid ovarian tumor measuring 13.9 cm × 11.8 cm on the right side and 10.0 cm × 6.3 cm on the left side with significant vascularity. Tumor markers were within normal limit except for significantly elevated serum lactate dehydrogenase. Magnetic resonance imaging showed two large solid homogeneous masses, hypointense on T1W1 and hyperintense on T2W1 imaging, with a normal sized uterus and no ascites or lymphadenopathy. The patient developed one episode of left hemiparesis preoperatively, which improved spontaneously. Staging laparotomy with total abdominal hysterectomy and bilateral salpingo-oophorectomy along with infracolic omentectomy was done. Histopathology with immunohistochemistry revealed primary T-cell lymphoblastic lymphoma of the ovary, involving both ovaries left fallopian tube and left serosal surface of fundal region of uterus. She developed generalized convulsions on the 12th postoperative day, and final diagnosis was primary ovarian T-cell lymphoblastic lymphoma Ann Arbor Stage IV. She received three cycles of chemotherapy with cyclophosphamide, doxorubicin, vincristine, and prednisolone regimen and was on palliative care. She succumbed to her illness 5½ months postoperatively.